Evaluation of changes in myocardial perfusion and function on exercise in patients with coronary artery disease by gated MIBI scintigraphy. Issue 1 (July 1993) - Avery, P; Hudson, N; Hubner, P
Abstract : OBJECTIVE–To investigate the ability of gated methoxy-isobutylisonitrile (MIBI) scintigraphy to measure changes in myocardial function as well as perfusion with exercise. SETTING–Regional cardiothoracic centre. PATIENTS–43 presenting with chest pain, 28 with coronary artery disease on angiography, and 15 with normal coronary arteriograms. RESULTS–Gated perfusion images showed an improvement in detecting regions with stenosed arteries compared with non-gated images (38/55 v 31/55, p < or = 0.01)). Functional analysis showed an increase in fractional shortening of 4.11% in subjects with normal coronary arteries, whereas in those with coronary disease a fall of 0.57% was found (p < or = 0.01). Both perfusion and function imaging showed an improved sensitivity compared with standard exercise testing (p < or = 0.01). When both function and perfusion imaging were analysed all patients with coronary disease were detected. There was agreement in abnormal regions in 33/55 territories supplied by a stenosed artery. Combined perfusion and function detected 49/55 (89%) of abnormal regions, thus improving the overall sensitivity from 38/55 (69%) by perfusion imaging alone (p < or = 0.01). CONCLUSIONS–Gated methoxy-isobutylisonitrile scintigraphy can successfully evaluate perfusion and function on exercise, so improving the diagnostic usefulness of this agent.